Recontextualisation of genre-based pedagogy: The case of Indonesian EFL classrooms - Kartika-Ningsih, Harni; Gunawan, Wawan (Universitas Pendidikan Indonesia, 2019)
Genre-based pedagogy has been adapted to the Indonesian national curriculum for subject English since 2004. There has been reports of its success and it now remains as an important part of the language curriculum at schools. However, there is a couple of considerations need to be taken seriously in relation with genre-based adaptation. First, genre-based pedagogy, based on systemic functional linguistics (SFL) theory, was developed in Australia in English as a mother tongue and ESL classrooms. Indonesian classrooms are different from those in Australia, not least because they teach English as a foreign language. Secondly, the Indonesian curriculum is prescribed from the centre, and though teachers are required to follow the genre-based approach that has been adopted, it is not clear how well teachers have understood it or implemented it. This article aims to discuss critically the recontextualisation of genre-based pedagogy in the EFL classrooms in Indonesia by investigating the ways teachers interpret and implement the teaching of English under the genre-based pedagogy. The study reported here was drawn from an action research project and involved observing one teaching learning unit of the teachers trained to implement the genre-based pedagogy. The findings indicate that the genre-based pedagogy in Indonesian EFL classrooms has been recontextualised only in part, because the influence of other teaching methods tends to prevail. This is problematic to the interest of the national curriculum to improve students’ English literacy. The main goal of genre pedagogy which aims to uphold social justice through equal distribution of knowledge will not prevail if the principles of the pedagogy itself is not recontextualised properly.